The Advantages of High-Lime Slags in the Smelting of Lead Ores (61e75f02-121b-4343-a628-ab8e7982e2d0) - S. E. Bretherton (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1915)
Discussion of the paper of S. E. BRETHERTON, presented at. the San Francisco meeting, September, 1915, and printed in Bulletin No. 104, August, 1915, pp. 1595 to1599. ANTON EILERS, Brooklyn, N. Y. (communication to the Secretary*). While the advantages in the use of high-line siliceous slags in lead smelting which Mr. Bretherton discusses in this paper are obvious under certain economical conditions, he gives me credit for the introduction of such slags when it does not belong to me. It is true I did considerable experimental work, off and on, for the purpose of finding such slags, while at the Germania in 1877 and 1878, but I did not have occasion to introduce any such slags for regular work, because I had no ores which fitted the economical conditions for using high silica and high lime, except in isolated cases for very brief periods. On the contrary, the ores I had to treat were mostly very ferruginous and very low in silica, so that, economically, I was compelled to run nearly always on slags, which allowed me to use the abundant flux I had without cost. It was August Raht who first had occasion to establish and use for long periods a slag high in silica and line, and low in iron. This was when he was confronted with the task of smelting the. Horn-Silver ores at the smelting works at Franklin, Utah, with as little expenditure for fluxing material as possible. I was at that time in Leadville, Col., where, in the new works I had built, the Billings and Eilers smelters, I had occasion to use profitably many slags, but never anything as high in the earthy bases and in silica as Mr. Raht had to use.